Surgical treatment of grade III gynecomastia with the horizontal scar technique and transposition of the nipple-areolar complex - “No vertical scar” - Lincoln Graça Neto; Rebeca Koteski; Ana Clara Minguetti Graça (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: The demand for surgery to correct gynecomastia has increased due to the many patients undergoing bariatric treatments. Most patients require extensive removal of excess skin, and fatty tissue, repositioning the nipple-areolar complex, and adjusting the areola volume. This study aims to describe the correction technique for grade III gynecomastia using a horizontal scar without a vertical scar, with repositioning of the nipple-areolar complex. Method: Prospective study of 27 male patients diagnosed with Simon grade III gynecomastia, operated in a private clinic between January 2013 and August 2020, using the horizontal scar technique with transposition of the nipple-areola complex and without a vertical scar. Results: 27 patients underwent surgery over 7.5 years, all ex-obese, previously submitted to weight loss treatment. Age ranged from 17 to 74 years, mean age of 52 years. The weight of the removed parts ranged from 175 to 758 grams, an average of 376 grams. Complications were 1 case of late hematoma (3.7%), 1 case of seroma (3.7%), and 2 cases of hypertrophic scarring (7.4%). Conclusion: Surgical treatment of grade III gynecomastia using the horizontal scar technique, without a vertical scar and with repositioning of the nippleareolar complex, proved to be effective, with low morbidity and good aesthetic results.